ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS INFORMASI LAPORAN KEUANGAN PEMERINTAH DAERAH (Studi Empiris Pada SKPD Pemerintah Kabupaten Kepulauan Talaud) - Modo, Sintike Mentari; Saerang, David Paul Elia; Poputra, Agus Tony (JURNAL RISET AKUNTANSI DAN AUDITING "GOODWILL", 2016)
The research was conducted on the basis of the gap between expectations and reality . Hope, by improving the quality of human resources and improvement of legislation in the field of financial management areas, generating financial reports quality information. In fact, the quality of financial reporting information in Talaud Islands District Government showed no significant developments. This is evidenced by the BPK opinion obtained by the Government of Talaud Islands during 2006 through 2015 that Gives Opinion, Unusual, and Fair With Exceptions. Opinion adopted by Talaud Islands raises the question of why the quality of financial reporting information local governments do not progress. Based on the research objective, this study can be categorized in the associative causal type. The location study performed in Talaud Islands District Government. Data used in this study are primary data. Data collection is done by distributing questionnaires to Financial Management (User Administration Budget and Finance Officer) on regionalÂ  work units (SKPD ) in Talaud Islands District Government. The population used was theÂ  financial manager in each SKPD, used as a sample 146 respondents. Data were analyzed using multiple linear regression analysis. The results showed that the Internal Monitoring , Understanding Regulation , Capacity Human Resources (HR), Use of Information Technology, and Organizational Commitment together have a significant effect on the Information Quality Local Government Finance Report (LKPD ), but the partial test results shows that only the Internal Control, Capacity Human Resources ( HR) Organizational commitment has a positive and significant impact on Quality of Information in Local Government Finance Report ( LKPD) . Keywords: Internal Control, Understanding Regulation, Capacity Human Resources, Use of Information Technology, Organizational Commitment, Quality of information in Local Government Financial Report.